Genetic relationship between bacteria isolated from intraoperative air samples and surgical site infections at a major teaching hospital in Ghana. Issue 3 (March 2020) - Stauning, M.A.; Bediako-Bowan, A.; Bjerrum, S.; Andersen, L.P.; Andreu-Sánchez, S.; Labi, A-K.; Kurtzhals, J.A.L.; Marvig, R.L.; Opintan, J.A.
Summary: Background: In low- and middle-income countries (LMICs) the rate of surgical site infections (SSI) is high, leading to negative patient outcomes and excess healthcare costs. A causal relationship between airborne bacteria in the operating room and SSI has not been established, at a molecular or genetic level. We studied the relationship between intraoperative airborne bacteria and bacteria causing SSI in an LMIC. Methods: Active air sampling using a portable impactor was performed during clean or clean-contaminated elective surgical procedures. Active patient follow-up consisting of phone calls and clinical examinations was performed 3, 14 and 30 days after surgery. Bacterial isolates recovered from SSI and air samples were compared by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF) identification, ribotyping, whole genome sequencing (WGS), and metagenomic analysis. Results: Of 128 included patients, 116 (91%) completed follow-up and 11 (9%) developed SSI. Known pathogenic bacteria were isolated from intraoperative air samples in all cases with SSI. A match between air and SSI isolates was found by MALDI-TOF in eight cases. Matching ribotypes were found in six cases and in one case both WGS and metagenomic analysis showed identity between air- and SSI-isolates. Conclusion: The study showed high levels of intraoperative airborne bacteria, an SSI-rate of 9% and a genetic link between intraoperative airborne bacteria and bacteria isolated from SSIs. This indicates the need for awareness of intraoperative air quality in LMICs.